Increasing Teacher Capacity Using a Project-Based Learning Model in the Implementation of the Independent Curriculum Through Teacher Working Groups at SD Negeri Tukharjo Samigaluh, Kulon Progo Regency, Academic Year 2022-2023 - Hertanto, Redemtus (Universitas Islam Indonesia, 2024)
This research aims to improve teachers' abilities in using the project-based learning model in implementing the independent curriculum at SD Negeri Tukharjo Kapenewon Samigaluh, Kulon Progo Regency. This research is school action research using a project-based learning model carried out in two cycles where each cycle consists of 2 meetings. The research procedures used include planning, implementing actions, reflecting and following up. Data collection techniques through observation and documentation. Data collection used instruments in the form of participant observation sheets related to the ability to use project-based learning models as well as the ability to implement school teacher working groups for resource persons. The research results in cycle I for the 1st meeting were categorized as very satisfactory.